1993
DOI: 10.1136/bmj.306.6884.1030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence screening for ovarian cancer in postmenopausal women by CA 125 measurement and ultrasonography.

Abstract: Objective-To assess the performance of the sequential combination of serum CA 125 measurement and ultrasonography in screening for ovarian cancer.Design-The serum CA 125 concentration of each subject was determined and those with a concentration : 30 U/ml were recalled for abdominal ultrasonography. If ultrasonography gave abnormal results surgical investigation was arranged. Volunteers were followed up by annual postal questionnaire.Setting-General practice, occupational health departments, ovarian cancer scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(84 citation statements)
references
References 17 publications
2
74
2
6
Order By: Relevance
“…The combination of CA-125 and TVU was tested before in the general population Menon et al, 1999) and was shown to be a feasible screenings method. However, failure to detect more than 57% of early-stage disease is cited as the major limitation of this type of screening (Jacobs et al, 1993). More studies are required to establish in a large group of high-risk patients the sensitivity, specificity and predictive value of ovarian cancer screening, by means of pelvis examination, transvaginal ultrasound and serum CA-125 determination.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of CA-125 and TVU was tested before in the general population Menon et al, 1999) and was shown to be a feasible screenings method. However, failure to detect more than 57% of early-stage disease is cited as the major limitation of this type of screening (Jacobs et al, 1993). More studies are required to establish in a large group of high-risk patients the sensitivity, specificity and predictive value of ovarian cancer screening, by means of pelvis examination, transvaginal ultrasound and serum CA-125 determination.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of screening with CA125 was initially improved by the use of pelvic ultrasound as a second-line test to assess ovarian volume and morphology. Using multimodal screening incorporating sequential CA125 and pelvic ultrasound, a specificity of 99.9% and PPV of 26.8% (Ďł4 operations for each cancer) for detection of ovarian and fallopian tube cancer was achieved in 22,000 postmenopausal women (63,64). With the accumulation of data in this study, ovarian morphology has been used to refine algorithms for the interpretation of ultrasound in postmenopusal women with elevated CA125 levels (65,66).…”
Section: Ovx1mentioning
confidence: 99%
“…The mean PI 16,18,24 in the benign and malignant group was significantly different. Based on receiver operating characteristics curve with area under curve of 95% confidence interval, the best cut off for PI was 0.8 which has a sensitivity of 96%, specificity of 81%,positive predictive value 76%,negative predictive value 97% and P value of <0.05 was obtained which was statistically significant.…”
Section: Statistical Analysis Of Pulsatility Indexmentioning
confidence: 93%